Thermally activated delayed fluorophore and plasmonic structures integrated with perovskites for X-ray scintillation and imaging - Jana, A; Cho, S; Sasikumar, K; Ju, H; Im, H; Taylor, RA (Cell Press, 2024)
The development of inexpensive and easily processable X-ray-sensitive materials is of great importance because a number of commercial scintillators, such as LaBr3(Ce), Gd3Al3Ga2O12(Ce), Cs2HfCl6, NaI:Tl, CsI:Tl, and LiI:Eu, are fabricated using highly toxic or rare-earth elements via high-temperature synthesis. This has spurred research into radioluminescence-enhancing mechanisms and solution-processable scintillating materials made from earth-abundant elements that have excellent optoelectronic properties, including high quantum yields and a low afterglow effect. In recent years, a range of metal halide perovskite (MHP) integrated with thermally activated delayed fluorescence (TADF) materials have been developed, exhibiting excellent scintillation properties and a high spatial resolution. Meanwhile, plasmonic technologies are reported to exploit light-energy confinement capabilities beyond the diffraction limit that produces local-field enhancement. This enhancement has subsequently improved the performance of small-sized optoelectronic devices such as solar cells and diagnostic optical sensors. This perspective summarizes the current development of innovative MHP, TADF, and plasmonic materials for use in scintillators and their integrated moieties while also identifying the relevant challenges. Following a thorough evaluation of the efforts made to improve the X-ray scintillation efficiency of these materials, we propose an outlook for future research in order to further enhance their scintillation properties and spatial resolution.